Do We Need a GCC Bank to Facilitate the Economic Turnaround of the GCC Region?. (28th July 2017) - Saxena, Stuti; Al‐Hadrami, Aflah Said Nasser
Abstract: Amidst the ongoing crisis of plummeting oil prices, the GCC (Gulf Cooperation Council) terrain has become a haunt of economists and financial analysts to tackle the ongoing challenges in the region. GCC constituents are gearing themselves with a robust political will that they hope could result in a turnaround of their economy by adopting a policy of economic diversification in nonoil‐based sectors. With this background supported by extensive qualitative scan of literature pertaining to the reforms proposed by the six members of the GCC to drive the economy forward amidst ongoing economic crisis, this article seeks to underscore the prospect of a shared initiative by the GCC constituents in institutionalizing a GCC bank as a potent innovative solution which may serve to provide an edifice for pushing forth the region's economy in nonhydrocarbon segments contingent upon the individual needs of the GCC constituents. As an exploratory study, this paper sheds light on these issues besides discussing the fundamental functions of the GCC bank.